Kajetan Gantar (1930–2022) - Stanonik, Marija (Slavia Centralis, 2022)
The author describes the work of the deceased Slovenian literary historian, classical philologist, translator and editor Kajetan Gantar and highlights his importance.
Keywords: Kajetan Gantar; in memoriam; classical philology; literary history; translating